Feeding programs to induce molting in Japanese quails (Coturnix japonica) - Faitarone, A. B. G. [UNESP] (2008)
The experiment was carried out in the experimental poultry house of the Research and Development Unit of Brotas of Agência Paulista de Tecnologia dos Agronegócios do Centro-Oeste, SP, Brazil. The objective of the study was to evaluate forced-molting methods and their effects on body weight, egg production, feed intake, and mortality, as well as bird performance during the second laying cycle. A total number of 400 65-week-old Japanese quails was distributed in a completely randomized experimental design into five treatments, with four replicates of 20 birds each. The following treatments were applied: T1= not submitted to forced molting, T2= 01 day of fasting + 13 days receiving 15g feed/bird/day (1F+R), T3= 02 days of fasting + 12 days receiving 15g feed/bird/day (2F+R), T4= 03 days of fasting + 11 days receiving 15g feed/bird/day (3F+R), and T5= 3 days of fasting and fed ad libitum thereafter (3F+AL). Significant differences were detected among treatments. When submitted to 3 days of fasting followed by ad libitum feeding, birds presented complete body weight recovery. No egg production percentage differences were detected in birds submitted to forced molting.